(untitled) (Reading, Mass., 1994)
This book is extremely clear and concise in explaining the basic level calculus. The addded instruction on how to use calculus on a calculator is a nice touch and ensures that the book is up to date. the organization of the material is logical and the difficulty level is perfect for a teacher to teach. It is a good text.
Keywords: Calculus,Tính toán